MEDIATING EFFECT OF VIDEO-ON-DEMAND ON XXI’S CUSTOMER PERCEIVED VALUE AND LOYALTY - Teta Maharani Paramitha; Henry Susanto Pranoto (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2023)
Disruption has become the main reason for abandoning conventional ways of modernization. This phenomenon also applies to the entertainment industry, where cinemas compete with subscription video-on-demand (SVOD). The largest cinema industry in Indonesia, Cinema XXI, is undoubtedly not resistant to this disruption. This research study applies a sample of 215 respondents from the sliced population of Cinema XXI customers and SVOD services subscribers. It aims to review the mediating effect of subscription video-on-demand services on the relationship between customer perceived value and customer loyalty to Cinema XXI. This study is a quantitative research, applying the Structural Equation Modeling (SEM) analysis method. Primary data was taken directly from the respondents using a Google Form-based questionnaire and later analyzed using JASP software. The results of the study show that subscription videos on demand do not have a significant mediating effect on the relationship between customer perceived value and customer loyalty. Subscription video on demand does not have a significant effect on customer loyalty. Though without a mediation, customer perceived value directly affects customer loyalty and subscription video on demand.